2007
DOI: 10.1158/0008-5472.can-06-4068
|View full text |Cite
|
Sign up to set email alerts
|

Repression of IFN Regulatory Factor 8 by DNA Methylation Is a Molecular Determinant of Apoptotic Resistance and Metastatic Phenotype in Metastatic Tumor Cells

Abstract: Apoptotic resistance is often associated with metastatic phenotype in tumor cells and is considered a hallmark of tumor progression. In this study, IFN regulatory factor 8 (IRF8) expression was found to be inversely correlated with an apoptotic-resistant and metastatic phenotype in human colon carcinoma cell lines in vitro. This inverse correlation was further extended to spontaneously arising primary mammary carcinoma and lung metastases in a mouse tumor model in vivo. Exogenous expression of IRF8 in the meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
103
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(116 citation statements)
references
References 49 publications
(66 reference statements)
8
103
2
2
Order By: Relevance
“…This is consistent with earlier reports showing that IRF8 is silenced in colorectal cancer cell lines in a DNA methylation-dependent manner. (23) In contrast to the data obtained with cell lines, we did not find an increase in IRF8 methylation in primary gastric cancers, as compared to noncancerous tissues. This is in contrast to earlier studies showing that IRF8 is methylated in cancers of the colon, esophagus, and nasopharyngus.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This is consistent with earlier reports showing that IRF8 is silenced in colorectal cancer cell lines in a DNA methylation-dependent manner. (23) In contrast to the data obtained with cell lines, we did not find an increase in IRF8 methylation in primary gastric cancers, as compared to noncancerous tissues. This is in contrast to earlier studies showing that IRF8 is methylated in cancers of the colon, esophagus, and nasopharyngus.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with that idea, a number of earlier studies have shown that IRFs are silenced by DNA methylation in human neoplasias. (23)(24)(25)37,38) Here, we found that DNA methylation of IRF4, IRF5, and ⁄ or IRF8 is a frequent event in gastric cancer cell lines and that treatment with a demethylating agent (DAC) restores induction of IRF5 by p53, p63, or p73 and induction of IRF8 by IFN-c, which confirms the role played by DNA methylation in silencing the genes. Moreover, when applied together, interferon and DAC acted synergistically to suppress cell growth.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…[39][40][41] In AML, 7 out of 21 analyzed samples showed signs of promoter methylation. 42 However, high expression of IRF8 in the presence of methylated promoter has been reported for leukemic cell lines.…”
Section: Wt1 Expression Does Not Affect the Methylation Of The Irf8 Pmentioning
confidence: 99%
“…In melanoma, for instance, one of the standard treatments is interferon, which induces tumor apoptosis, differentiation and increases the anti-tumor immune response. Silencing of genes involved in signaling downstream of interferon, such as interferon regulatory factor 8 and XIAPassociated factor 1 trigger resistance of tumor cells to interferon therapy (Reu et al, 2006;Yang et al, 2007). However, injection of decitabine in nude mice carrying melanoma xenografts led to resensitization to interferon treatment (Reu et al, 2006).…”
Section: Epigenetic Cancer Therapymentioning
confidence: 99%